Development of Current Collector for Low-speed Maglev Train - CHEN Mingguo; ZHOU Jie; BAI Xue (机车电传动)
Aiming at the current collector design requirements for technical specifications of low-speed maglev train, the company independently developed current collector of maglev train was introduced, including its main parameters, structure and design feature, as well as the parameters of the spring and contact force were calculated. The structure of current collector adopted a parallelogram four bar linkage with highly reliability and stability. Prototype manufacture, testing and running on maglev train showed that the designed and developed current collector could meet the requirements of the maglev train specification with the advantages of good performances and high reliability.